Political Brand Architecture Management: A Resource Allocation Perspective in Ghana - Amenuvor, F.E. (University of Ghana, 2015)
Political brand architecture management is described as a strategic approach of arranging and rearranging the political brand elements in a way that best meets the unique characteristics of the target voter. The idea behind this approach, which is borrowed from the brand architecture theory in branding, is to ensure that political parties do due diligence in allocating campaign resources effectively and appropriately. Although several studies have been conducted in both the Western and Ghanaian contexts on political branding, none has yet studied the relationship between political brand architecture management and resource allocation while accounting for the influence of other factors such as social, economic, technological and cultural issues. The main objective of the study is to ascertain the relationship between political brand architecture management and resource allocation. The research adopts a mixed method approach that uses both qualitative and quantitative means to collect and analyse data. It makes use of in-depth interviews, analysis of media items, thematic analysis as well as correlation and multiple regression analysis to investigate the relationship among political brand architecture management, effective resource allocation and political party performance in the Ghanaian context. Five hundred (500) registered voters drawn from five different constituencies in Accra, Ghana that cut across both lower and upper classes were sampled for this research using stratified and convenience sampling techniques respectively. Again, purposive sampling was used to select the four (4) political parties for the focus interviews, which centred on their resource allocation approach and the level to which they have adopted brand architecture. The outcome of the research shows that political brand architecture management has a significant positive impact on political party performance. The research also revealed that political brand architecture management has a significant positive impact on effective resource allocation. Another objective of the research was to empirically test the impact of effective resource allocation on political party performance and the results shows that there is a significant positive effect of effective resource allocation on political party performance. The research therefore concludes that, if political parties strategically manage the political brand architecture, it will lead to an effective allocation of resources, which will eventually lead to an enhanced electoral performance. The implications of the study and its findings, as related to theory and practice, were also discussed.
Thesis (MPhil) - University of Ghana, 2015